POLYCURRENCY BASKET AS THE NEW REFERENCE POINT OF THE COURSE POLICY OF BANK OF RUSSIA - G.V. KHATUSCHENKO (Advanced Engineering Research, 2007)
The article is devoted to transformation of a course policy of Bank of Russia and introduction of "a basket of currencies " consisting of Euro and US dollar. Since February, 2005 the currency basket is one of major factors of a monetary and credit policy of Bank of Russia influencing on formation of a real rouble exchange rate. Transition to use of an bicurrency operational reference point is directed on decrease(reduction) of intraday volotation of a rouble exchange rate to significant for the Russian Federation foreign currencies. In process of adaptation of participants of the currency market to new conditions the Central Bank changes a share ratio of dollar and euro in "a basket of currencies". Besides the bicurrency basket is one of tools of Bank of Russia for restraint of growth of parameters of inflation.